Diseño gráfico para la puesta en valor de la memoria de la parroquia Mulliquindil cantón Salcedo, provincia de Cotopaxi. - Masapanta Hinojosa, Damián Darío (2019)
The research work was carried out to develop the knowledge of the inhabitants of the Mulliquindil parish, because they do not know how the process of transculturation and hybridization has been in the sector, taking into account that there are no visual contents that provide this type of information, the production of local development in the sector was also discussed and how each of the activities generated and adopted by the villagers that they have enabled the parish to be a prosperous place and serve as a reference for other sectors; the proposal of the visual content stands its information and objectives, investigating the current situation of the sector, all the physical aspects that allow to make a contrast with the Mulliquindil of the 60s and 70s, to carry out this process, data collection techniques such as: observation, interviews, focus group. It was proposed to carry out a bibliographic research in which research can be sustained, but above all learn to use terms that can structure a technical content, which can be culminated with the contribution of disciplines such as photography, illustration, editorial design which they allow to materialize all the research content, taking into account that the disciplines mentioned adhere to the research methodology applied to the project, proposed by Bruce Archer, which allows analyzing, creating and executing a beneficial alternative for the place of execution. A relevant point of the research is how it will encourage the criteria and concepts of both the inhabitants of Mulliquindil and society in general who take as reference to the sector, evidencing the traditions, cultural, social, sports, agricultural activities, which form part of the visual content which is based on the progress of the Santaneros and their land.